2015
DOI: 10.1007/978-1-4939-2815-6_14
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Plasmodium falciparum Erythrocyte Invasion Phenotypes Using Flow Cytometry

Abstract: Having the ability to rapidly, accurately, and robustly measure Plasmodium falciparum merozoite invasion is a critical component in effective assessment of a blood stage vaccine's mechanism of action. Being able to measure invasion of erythrocytes accurately, objectively and in a high throughput fashion is of critical importance. Here, we describe a simple and robust flow cytometry method that allows for the measurement of the key invasion parameters of parasite multiplication rate and erythrocyte selectivity-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
(13 reference statements)
1
8
0
Order By: Relevance
“…Two-color FCM is the most widely used method for phenotyping parasite invasion pathways as it offers minimal handling of donor infected culture. However, current protocols require samples of field isolates at ∼1% parasitemia for assay set-up (Bei and Duraisingh 2015), which are more uncommon in low transmission settings. This study presents a modification of current protocols to enable the determination of invasion pathways for field isolates at low parasitemia with improved sensitivity and reproducibility.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Two-color FCM is the most widely used method for phenotyping parasite invasion pathways as it offers minimal handling of donor infected culture. However, current protocols require samples of field isolates at ∼1% parasitemia for assay set-up (Bei and Duraisingh 2015), which are more uncommon in low transmission settings. This study presents a modification of current protocols to enable the determination of invasion pathways for field isolates at low parasitemia with improved sensitivity and reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…SYBR Green I has a low binding affinity for RNA and so, will preferentially bind DNA given the shortest time possible. This study protocol reported a reduced parasite DNA staining time with SYBR Green 1 down to 20minutes, from 1 hour used in the conventional protocols (Theron et al 2010; Bei and Duraisingh 2015). The limit of quantification of reinvasion parasitemia was accurate to 0.05% parasitemia from a 1:1 assay of 0.02% well parasitemia (>2-fold increase after a single cycle of growth).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations